2013
DOI: 10.1002/hep.25688
|View full text |Cite
|
Sign up to set email alerts
|

Case-control study of hepatitis B and hepatitis C in older adults: Do healthcare exposures contribute to burden of new infections?

Abstract: Reports of hepatitis B virus (HBV) and hepatitis C virus (HCV) transmission associated with unsafe medical practices have been increasing in the United States. However, the contribution of healthcare exposures to the burden of new infections is poorly understood outside of recognized outbreaks. We conducted a case-control study at three health departments that perform enhanced viral hepatitis surveillance in New York and Oregon. Reported cases of symptomatic acute hepatitis B and hepatitis C occurring in perso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 28 publications
0
29
1
1
Order By: Relevance
“…The incidence of surgery-associated HCV infections caused by breaches in infection control practices have been previously reported in the USA. 31 In the current study, many of the surgeries reported by CHC patients were performed before routine HCV screening was initiated prior to invasive surgeries. In addition, many of the surgeries were carried out abroad; as such, adherence to blood-borne pathogen screening protocols at such institutions was unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of surgery-associated HCV infections caused by breaches in infection control practices have been previously reported in the USA. 31 In the current study, many of the surgeries reported by CHC patients were performed before routine HCV screening was initiated prior to invasive surgeries. In addition, many of the surgeries were carried out abroad; as such, adherence to blood-borne pathogen screening protocols at such institutions was unknown.…”
Section: Discussionmentioning
confidence: 99%
“…143 Several recent outbreaks involving patient-to-patient HBV transmission have been recorded. [144][145][146] Outbreaks mostly occurred in renal ward/hemodialysis patients and were frequently related to lack of infection control measures. 145,146 Transmission from HCWs to patients has also been observed.…”
Section: Benefits and Risks In Healthcare Settingsmentioning
confidence: 99%
“…[144][145][146] Outbreaks mostly occurred in renal ward/hemodialysis patients and were frequently related to lack of infection control measures. 145,146 Transmission from HCWs to patients has also been observed. 147 The risk of HCWs acquiring HBV infection is related to the extent of percutaneous or mucosal exposure to blood and other bodily fluids.…”
Section: Benefits and Risks In Healthcare Settingsmentioning
confidence: 99%
“…1,2 Several medical procedures have been associated with HCV transmission, being haemodialysis the most frequently reported one. [3][4][5] Transmission during colonoscopy procedures has also been reported.…”
Section: Introductionmentioning
confidence: 99%